Rheumatoid factor and antibodies against cyclic citrullinated peptide in patients without rheumatoid arthritis - N. V. Bunchuk (Klinicist)
A review of data on the possible causes of an increase rheumatoid factor (RF), antibodies against cyclic citrullinated peptide (ACCP) and antibodies to modified citrullinated vimentin (AMCV) in patients without rheumatoid arthritis (RA) is presented. The possibility of hyperproduction of these autoantibodies before the development of the clinical picture of RA was indicated. It is indicated that ACCP and IgA RF have the greatest prognostic value in terms of the subsequent development of RA. These antibodies are recommended to be additionally determined in diagnostically difficult cases. Data on the sensitivity and specificity of detection of RF, ACCP and AMCV in the diagnosis of RA are summarized. The results of detection of the discussed antibodies in various rheumatic (other than RA) and non-rheumatic diseases are presented in detail. Particular attention is paid to diseases in which increased synthesis of RF, ACCP and AMCV may not be accompanied by clear clinical symptoms (Sjögren’s disease, autoimmune thyroiditis, some chronic infections, silicosis, monoclonal gammopathy, etc.). Recommendations are given for examining patients with “accidentally” identified increase in RF or ACCP.